Heart failure in Acute Coronary Syndrome: predictors and prognosis. (11th May 2021) - Santos, M; Santos, H; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Tavares, J; Santos, L; Almeida, ML
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: on behalf of the Investigators of " Portuguese Registry of ACS " Introduction: Heart failure (HF) is a frequent complication of acute coronary syndromes (ACS). Therefore, it is important to access its impact on prognosis and identify patients (pts) with higher risk of HF. Objective: To evaluate predictors and prognosis of HF in the setting of ACS. Methods: Based on a multicenter retrospective study, data collected from admissions between 1/10/2010 and 4/09/2019. Pts without data on cardiovascular history or uncompleted clinical data were excluded. Pts were divided in 2 groups (G): GA – pts without HF; GB - pts with HF during hospitalization. Results: HF occurred in 4003 (15.6%) out of 25718 pts with ACS. GB was older (74 ± 12 vs 65 ± 13, p < 0.001), had more females (36.3% vs 26.2%, p < 0.001), had higher rates of arterial hypertension (78.4% vs 69.3%, p < 0.001), dyslipidaemia (64.4% vs 61.1%. p < 0.001), previous ACS (25.6% vs 19.7%, p < 0.001, ), previous HF (16.4% vs 4.1%, p < 0.001), previous stroke (11.9% vs 6.4%, p < 0.001), chronic kidney disease (CKD) (17.1% vs 5.5%, p < 0.001), chronic obstructive pulmonary disease (COPD) (7.8% vs 3.8%, p < 0.001) and longer times from first symptoms to admission (268min vs 238min, p < 0.001). GA had higher rate of smokers (28.4% vs 16.2%, p < 0.001) and higher rate of non-ST-elevation myocardial infarction (MI) (46.5% vs 43.0%, p < 0.001). GB had higher rates of ST-elevation MI (STEMI) (49.2% vs 41.1%, p < 0.001), namely anterior STEMI (58.1% vs 44.9%, p < 0.001). GB had lower blood pressure (130 ± 32 vs 140 ± 28, p < 0.001), higher heart rate (86 ± 23 vs 76 ± 18, p < 0.001), Killip-Kimball class (KKC) ≥2 (63.2% vs 6.7%, p < 0.001), atrial fibrillation (AF) (15.4% vs 5.7%, p < 0.001), left bundle branch block (7.5% vs 3.1%, p < 0.001) and were previously treated with diuretics (39.1% vs 22.1%, p < 0.001), amiodarone (2.2% vs 1.4%, p < 0.001) and digoxin (2.8% vs 0.7%, p < 0.001). GB had higher rates of multivessel disease (66.0% vs 49.5%, p < 0.001) and planned coronary artery bypass grafting (7.3% vs 6.0%, p < 0.001), reduced left ventricle function (72.3% vs 33.4%, p < 0.001) and needed more frequently mechanical ventilation (8.2% vs 0.9%, p < 0.001), non-invasive ventilation (8.7% vs 0.5%, p < 0.001) and provisory pacemaker (4.5% vs 1.0%, p < 0.001). Logistic regression confirmed females (p < 0.001, OR 1.42, CI 1.29-1.58), diabetes (p < 0.001, OR 1.43, CI 1.30-1.58), previous ACS (p < 0.001, OR 1.27, CI 1.10-1.47), previous stroke (p < 0.001, OR 1.35, CI 1.16-1.57), CKD (p < 0.001, OR 1.76, CI 1.50-2.05), COPD (p < 0.001, OR 2.15, CI 1.82-2.54), previous usage of amiodarone (p = 0.041, OR 1.35, CI 1.01-1.81) and digoxin (p < 0.001, OR 2.30, CI 1.70-3.16), and multivessel disease (p < 0.001, OR 1.64, CI 1.67-2.32) were predictors of HF in the setting of ACS. Event-free survival was higher in GA than GB (79.5% vs 58.1%, OR 2.3, p < 0.001, CI 2.09-2.56). Conclusion: As expected, HF in the setting of ACS is associated with poorer prognosis. Several features may help predict the HF occurrence during hospitalizations, allowing an earlier treatment.